Operationalization of a frailty index in patients with multiple sclerosis: A cross-sectional investigation. (October 2021) - Belvisi, Daniele; Canevelli, Marco; Baione, Viola; Buscarinu, Maria Chiara; Pellicciari, Giulia; Fantozzi, Roberta; Creta, Armando; Cecchi, Gianluca; Cola, Gaia; Nicoletti, Carolina Gabri; Cortese, Antonio; De Giglio, Laura; et al.
Background: Frailty is an age-related status of increased vulnerability to stressors caused by the accumulation of multiple health deficits. This construct may allow to capture the clinical complexity of patients with multiple sclerosis (MS). Objective: To investigate the relationship between frailty and the clinical manifestations of MS. Methods: Patients with MS were consecutively enrolled at five tertiary dedicated services. Disability and fatigue were assessed. The phenotypes of MS were also identified. Frailty was measured using a frailty index (FI), computed by cumulatively considering 42 age-related multidimensional health deficits. Results: Overall, 745 MS patients (mean age = 48.2 years, standard deviation = 11.7 years; women 68%) were considered. The median FI value was 0.12 (interquartile range = 0.05–0.19) and the 99th percentile was 0.40. FI scores were associated with MS disease duration, disability, fatigue, as well as with the number of previous disease-modifying treatments and current symptomatic therapies. A logistic regression analysis model showed that FI score was independently associated with the secondary progressive phenotype. Conclusion: Frailty is significantly associated with major characteristics of MS. The findings of the present cross-sectional investigation should be explored in future longitudinal studies.